THE IMPORTANCE OF LINGUOCULTUROLOGICAL RESEARCH (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article provides comments on the essence of linguoculturological research, its importance, compatibility with anthropocentric views, its connection with other disciplines, the theoretical foundations of work in this field, and its role in the development of linguistics.